Efficiency of cycling exercise: Quantification, mechanisms, and misunderstandings - MacDougall, K. B.; Falconer, T. M.; MacIntosh, B. R. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The energetics of cycling represents a well-studied area of exercise science, yet there are still many questions that remain. Efficiency, broadly defined as the ratio of energy output to energy input, is one key metric that, despite its importance from both a scientific as well as performance perspective, is commonly misunderstood. There are many factors that may affect cycling efficiency, both intrinsic (e.g., muscle fiber type composition) and extrinsic (e.g., cycling cadence, prior exercise, and training), creating a complex interplay of many components. Due to its relative simplicity, the measurement of oxygen uptake continues to be the most common means of measuring the energy cost of exercise (and thus efficiency); however, it is limited to only a small proportion of the range of outputs humans are capable of, further limiting our understanding of the energetics of high-intensity exercise and any mechanistic bases therein. This review presents evidence that delta efficiency does not represent muscular efficiency and challenges the notion that the slow component of oxygen uptake represents decreasing efficiency. It is noted that gross efficiency increases as intensity of exercise increases in spite of the fact that fast-twitch fibers are recruited to achieve this high power output. Understanding the energetics of high-intensity exercise will require critical evaluation of the available data.